Microflora, Contents of Polyamines, Biogenic Amines, and TVB-N in Bovine Offal and Game Meat for the Raw-Feeding of Adult Dogs - Sarah Lindinger; Susanne Bauer; Zuzana Dicakova; Brigitte Pilz; Peter Paulsen (Animals, 2023)
Microflora and contents of biogenic amines/polyamines and total volatile basic nitrogen (TVB-N) in 99 samples of bovine offal (red offal, n = 41 and other offal and mixes, n = 45) and wild game meat (n = 13) for raw meat-based diets (RMBD) for dogs were analyzed. Samples were bought in 11 local pet food shops and in one game-handling establishment in Austria (Lower Austria, Styria, and Vienna) in September and October 2022. Median contents (first and third quartiles in brackets) of cadaverine, histamine, tyramine, spermidine, and spermine were 20.7 [16.7; 28.6]; 25.4 [17.1; 47.2]; 18.9 [13.6; 38.9]; 15.2 [11.2; 21.2]; and 41.9 [<limit of detection; 64.5] mg/kg wet weight, respectively. The sum of putrescine + cadaverine + histamine + tyramine was >50 mg/kg in 85.9% of samples, indicating the use of low-quality ingredients or inappropriate storage conditions. However, only 10.1% of samples were determined to be not compliant with a maximum amine content proposed for pet food. Median contents of the total aerobic bacteria counts (TACs), Pseudomonas, and Enterobacteriaceae were 7.4 [6.4; 8.0]; 6.5 [5.5; 7.7]; and 4.8 [3.9; 5.6] log CFU/g, respectively, with significantly lower counts in red offal RMBD (p < 0.05). TVB-N exceeded 150 mg/kg in 87.9% of samples. The TACs and Enterobacteriaceae numbers in red offal RMBD were comparable to those in food-grade red offal after 6 days of aerobic storage at 7 °C, i.e., temperatures higher than required for food-grade offal, but acceptable for animal by-products intended for RMBD production. In 80.8% of samples, numbers of Enterobacteriaceae exceeded the EU legal limit. From 12 of these samples, Salmonellae was able to be isolated, with counts from 0.03 MPN/g to 110 MPN/g. Salmonella enterica ser. Montevideo (n = 3), and S. enterica ser. Give and S. enterica ssp. Diarizonae (n = 2 each) were the most frequently isolated, while Listeria monocytogenes was rarely recovered (2%). Whilst exposure of humans handling such pet food can be reduced by hygiene precautions, the risk remains that dogs can acquire a feed-borne salmonellosis and shed the pathogen.